Answer:
+3x + 7 to make the sum x3
Step-by-step explanation:
to find the sum of 3 and to solve it to get the value of x
Answer:
y(-4) = 5
y'(-4) = -7
Step-by-step explanation:
Hi!
Since the tangent line T and the curve y must coincide at x=-4
y(-4) = T(-4) = 5
On the other hand, the derivative of the curve evaluated at -4 y'(x=-4) must be the slope of the tangent line. Which inspecting the tangent line T(x) is -7
That is:
y'(-4) = -7
Answer:
x^2+x+1
Step-by-step explanation:
(3x^2+4x−1)+(−2x^2−3x+2)
Combine like terms
3x^2-2x^2+4x-3x-1+2
x^2+x+1